(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
Staff-Motivation remains one of the most studied and discussed topics among theorists and practitioners of management. Well-formed motivational system increases employees’ loyalty, increases their productivity and saves resources of the company. In order to create optimal motivation in the organization, it is necessary to study the needs of employees, taking into account, their generation.